Influência dos componentes da matriz alimentar e do pH do meio sobre o efeito inibitório do carvacrol frente Salmonella Typhimurium PT4 e Escherichia coli 0157H:7 - Carvalho, Rhayane Idalyne (2017)
The control of microbial growth in food is mainly achieved through the use of chemical preservatives. However, it has been reported that these agents could be toxic to humans and the environment, and their use has been increasingly limited. Carvacrol (CAR) is a phenolic monoterpene derived from plants with recognized antimicrobial activity against foodborne pathogens, such as Salmonella Typhimurium PT4 and Escherichia coli O157H: 7. The use of CAR as antibacterial in foods has been related as a viable alternative because its strong inhibitory effect at low concentrations when compared with other phenolic compounds. It is well-known that the composition of the food matrix, as well as the environmental conditions may influence on the activity of essential oil that possess CAR as the major constituent , however, a little is known regarding the effects of the food constituents and pH on the antimicrobial efficacy of CAR. This study was performed to assess the effects of proteins (PTN), lipids (LIP) and pH, as well as the interaction of these parameters on the inhibitory activity of CAR against S. Typhimurium PT4 and Escherichia coli O157:H7. To measure these effects, the minimum inhibitory concentration (MIC) of CAR, the specific maximum growth rate (μmax) and duration of the lag (λ) phase of the test strains when exposed to CAR in experimental cultivation media containing different amounts of PTN (4.0 g/100 mL, 6.0 g/100 mL and 8.0 g/100 mL) and LIP (3.75 g/100 mL, 5.0 g/100 mL and 6.25 mL/100 mL) at different pH values (5.0, 5.5 and 6.0) were determined. The viable cell counts of S. Typhimurium PT4 and Escherichia coli O157:H7 when exposed to CAR in experimental cultivation media that promoted the highest and the lowest μmax were also monitored over time. MIC values of CAR against S. Typhimurium PT4 and Escherichia coli O157:H7 in the experimental cultivation media assayed was up to four-fold higher (4.8 or 9.6 μL/mL) than those found in laboratory media (brain heart infusion broth (BHI 0.6 μL/mL). PTN concentration did not affect (p > 0.05) the inhibitory effects of CAR under the tested experimental conditions. The inhibitory effects of 2.4 or 4.8 of CAR μL/mL against both test strains was affected (p ≤ 0.05) by LIP and pH, and mostly by LIP-pH interaction. The increase in LIP amounts followed by increase in pH values enhanced the inhibitory effects of CAR regardless the tested CAR concentration (2.4 or 4.8 μL/mL). CAR at 2.4 or 4.8 μL/mL failed to inhibit S. Typhimurium PT4 and E. coli O157:H7 in experimental cultivation media that promoted the highest μmax of test strains. In experimental cultivation media where the lowest μmax values were observed, CAR showed bacteriostatic effects against S. Typhimurium PT4 and decreased the viable counts of E. coli O157:H7 over time. These results show that LIP concentration, pH and the interaction of LIP-pH could affects the of antibacterial activity CAR against foodborne pathogens, and suggest that the CAR concentration used in foods should be cautiously evaluated to achieve the expected antibacterial efficacy.